High temporal resolution modelling of environmentally-dependent seabird ammonia emissions: Description and testing of the GUANO model. (July 2017) - Riddick, S.N.; Blackall, T.D.; Dragosits, U.; Tang, Y.S.; Moring, A.; Daunt, F.; Wanless, S.; Hamer, K.C.; Sutton, M.A.
Abstract: Many studies in recent years have highlighted the ecological implications of adding reactive nitrogen (Nr ) to terrestrial ecosystems. Seabird colonies represent a situation with concentrated sources of Nr, through excreted and accumulated guano, often occurring in otherwise nutrient-poor areas. To date, there has been little attention given to modelling N flows in this context, and particularly to quantifying the relationship between ammonia (NH3 ) emissions and meteorology. This paper presents a dynamic mass-flow model (GUANO) that simulates temporal variations in NH3 emissions from seabird guano. While the focus is on NH3 emissions, the model necessarily also treats the interaction with wash-off as far as this affects NH3 . The model is validated using NH3 emissions measurements from seabird colonies across a range of climates, from sub-polar to tropical. In simulations for hourly time-resolved data, the model is able to capture the observed dependence of NH3 emission on environmental variables. With temperature and wind speed having the greatest effects on emission for the cases considered. In comparison with empirical data, the percentage of excreted nitrogen that volatilizes as NH3 is found to range from 2% to 67% (based on measurements), with the GUANO model providing a range of 2%–82%. The model provides a tool that can be used to investigate the meteorological dependence of NH3 emissions from seabird guano and provides a starting point to refine models of NH3 emissions from other sources. Highlights: A dynamic mass-flow model to simulate variation in NH3 emissions from seabird guano. Model output validated against measurements from colonies across a range of climates. Model output captures observed dependence of NH3 emission on environmental variables. This model can be a starting point to model NH3 emissions from other sources.